At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Let's solve the equation [tex]\(\frac{1}{2} m - \frac{3}{4} = x\)[/tex], where [tex]\(x\)[/tex] is one of the given values 20, 32, 44, or 48, to find the corresponding values of [tex]\(m\)[/tex].
### Step-by-Step Solution:
1. Start with the given equation:
[tex]\[ \frac{1}{2}m - \frac{3}{4} = x \][/tex]
2. Isolate [tex]\(m\)[/tex]:
To isolate [tex]\(m\)[/tex], we first need to get rid of the [tex]\(\frac{3}{4}\)[/tex] term by adding [tex]\(\frac{3}{4}\)[/tex] to both sides of the equation:
[tex]\[ \frac{1}{2}m = x + \frac{3}{4} \][/tex]
3. Solve for [tex]\(m\)[/tex]:
Now, we multiply both sides by 2 to solve for [tex]\(m\)[/tex]:
[tex]\[ m = 2 \left( x + \frac{3}{4} \right) \][/tex]
4. Substitute each value of [tex]\(x\)[/tex]:
Let's calculate [tex]\(m\)[/tex] for each given [tex]\(x\)[/tex] value one-by-one.
- For [tex]\(x = 20\)[/tex]:
[tex]\[ m = 2 \left( 20 + \frac{3}{4} \right) = 2 \left( 20.75 \right) = 41.5 \][/tex]
- For [tex]\(x = 32\)[/tex]:
[tex]\[ m = 2 \left( 32 + \frac{3}{4} \right) = 2 \left( 32.75 \right) = 65.5 \][/tex]
- For [tex]\(x = 44\)[/tex]:
[tex]\[ m = 2 \left( 44 + \frac{3}{4} \right) = 2 \left( 44.75 \right) = 89.5 \][/tex]
- For [tex]\(x = 48\)[/tex]:
[tex]\[ m = 2 \left( 48 + \frac{3}{4} \right) = 2 \left( 48.75 \right) = 97.5 \][/tex]
### Compiled Results:
- When [tex]\(x = 20\)[/tex], [tex]\(m = 41.5\)[/tex]
- When [tex]\(x = 32\)[/tex], [tex]\(m = 65.5\)[/tex]
- When [tex]\(x = 44\)[/tex], [tex]\(m = 89.5\)[/tex]
- When [tex]\(x = 48\)[/tex], [tex]\(m = 97.5\)[/tex]
Thus, the corresponding values of [tex]\(m\)[/tex] for the given [tex]\(x\)[/tex] values are:
[tex]\([41.5, 65.5, 89.5, 97.5]\)[/tex]
### Step-by-Step Solution:
1. Start with the given equation:
[tex]\[ \frac{1}{2}m - \frac{3}{4} = x \][/tex]
2. Isolate [tex]\(m\)[/tex]:
To isolate [tex]\(m\)[/tex], we first need to get rid of the [tex]\(\frac{3}{4}\)[/tex] term by adding [tex]\(\frac{3}{4}\)[/tex] to both sides of the equation:
[tex]\[ \frac{1}{2}m = x + \frac{3}{4} \][/tex]
3. Solve for [tex]\(m\)[/tex]:
Now, we multiply both sides by 2 to solve for [tex]\(m\)[/tex]:
[tex]\[ m = 2 \left( x + \frac{3}{4} \right) \][/tex]
4. Substitute each value of [tex]\(x\)[/tex]:
Let's calculate [tex]\(m\)[/tex] for each given [tex]\(x\)[/tex] value one-by-one.
- For [tex]\(x = 20\)[/tex]:
[tex]\[ m = 2 \left( 20 + \frac{3}{4} \right) = 2 \left( 20.75 \right) = 41.5 \][/tex]
- For [tex]\(x = 32\)[/tex]:
[tex]\[ m = 2 \left( 32 + \frac{3}{4} \right) = 2 \left( 32.75 \right) = 65.5 \][/tex]
- For [tex]\(x = 44\)[/tex]:
[tex]\[ m = 2 \left( 44 + \frac{3}{4} \right) = 2 \left( 44.75 \right) = 89.5 \][/tex]
- For [tex]\(x = 48\)[/tex]:
[tex]\[ m = 2 \left( 48 + \frac{3}{4} \right) = 2 \left( 48.75 \right) = 97.5 \][/tex]
### Compiled Results:
- When [tex]\(x = 20\)[/tex], [tex]\(m = 41.5\)[/tex]
- When [tex]\(x = 32\)[/tex], [tex]\(m = 65.5\)[/tex]
- When [tex]\(x = 44\)[/tex], [tex]\(m = 89.5\)[/tex]
- When [tex]\(x = 48\)[/tex], [tex]\(m = 97.5\)[/tex]
Thus, the corresponding values of [tex]\(m\)[/tex] for the given [tex]\(x\)[/tex] values are:
[tex]\([41.5, 65.5, 89.5, 97.5]\)[/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.